Pengaruh Kualitas Produk, Pelayanan, dan Harga terhadap Keputusan Pembelian Teh Ginastel di Surakarta - Riptanti, Erlyna Wida; Nurdiana; Sundari, Mei Tri (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2025)
The plantation subsector is one of the main components in the agricultural sector. Tea is one of the leading commodities from this subsector. One of the fast-growing tea-based beverage businesses is Ginastel Tea, located in Surakarta City. This study aims to examine the effect of product quality, service quality, and price on purchasing decisions for Ginastel Tea in Surakarta. The research was conducted using quantitative analysis method, where the research location was selected using purposive sampling technique. Data were collected through observation, interviews, and recording using a questionnaire. Determination of the number of samples was also carried out by purposive sampling, involving 150 respondents. The Structural Equation Modeling (SEM) method with the Partial Least Square (PLS) approach was used as data analysis. The results showed that product quality and price significantly influenced the purchase decision of Ginastel Tea, while service quality had no significant effect. In addition, consumer trust in Ginastel Tea is one of the factors that encourage consumers to prefer this product over other tea drinks. Consumers tend to consider product quality in purchasing decisions and assess that the price of Ginastel Tea is comparable to the quality offered, not much different from other tea brands.